A critical assessment of retail sovereign sukuk in Indonesia. (18th July 2019) - Sukmana, Raditya
Abstract : Purpose: The purpose of this paper is to critically evaluate the retail sovereign sukuk in Indonesia, which so far is not found elsewhere in the world and is an effective instrument to raise funds for covering government budget deficits. Design/methodology/approach: The paper adopts qualitative research combining literature studies, valid data from sukuk.com, government official documents and also in-depth interviews with relevant government officials to strengthen the arguments. Findings: Competitive rates, ability to be bought by individual and risk-free funding are some of the specific features of sukuk, while economic growth and large populations are some of the key success factors. Practical implications: This study will be the main reference for other governments which are keen to adopt similar instruments for their respective countries. Social implications: As individual is eligible to buy this sukuk, this may lead to a better wealth distributions Originality/value: To the best of the author's knowledge, this paper is the first to comprehensively and critically evaluate the one and only retail sovereign sukuk as an alternative government instrument to raise funds.